Islamophobia and Twitter: A Typology of Online Hate Against Muslims on Social Media. Issue 2 (June 2014) - Awan, Imran
<x xml:space="preserve">Abstract</x> The Woolwich attack in May 2013 has led to a spate of hate crimes committed against Muslim communities in the United Kindom. These incidents include Muslim women being targeted for wearing the headscarf and mosques being vandalized. While street level Islamophobia remains an important area of investigation, an equally disturbing picture is emerging with the rise in online anti‐Muslim abuse. This article argues that online Islamophobia must be given the same level of attention as street level Islamophobia. It examines 500 tweets from 100 different Twitter users to examine how Muslims are being viewed and targeted by perpetrators of online abuse via the Twitter search engine, and offers a typology of offender characteristics.